Pengaruh Interpersonal Interactions terhadap Purchase Intention pada TikTok Shop Live Streaming - Margaretta, Melissa; Andajani, Erna; Novika, Fitri (SAFE-Network, 2024)
This study aims to analyze the influence of perceived expertise, perceived similarity, perceived familiarity, perceived likability, perceived informativeness, perceived responsiveness, and swift guanxi that can affect purchase intention in shopping on TikTok Shop through live streaming. The research uses a quantitative method. A survey was conducted by distributing a questionnaire via Google Forms to 327 respondents. The data were analyzed using Smart PLS 4.0. The study found that swift guanxi occurring during live streaming influences purchase intention. The results also showed that perceived expertise, perceived similarity, perceived likeability, perceived informativeness, and perceived responsiveness influence swift guanxi, thereby increasing purchase intention. Meanwhile, perceived familiarity does not affect swift guanxi.